Primary intraocular lymphoma: a review of the clinical, histopathological and molecular biological features - Coupland, Sarah E.; Heimann, Heinrich; Bechrakis, Nikolaos E. (Graefe's archive for clinical and experimental ophthalmology, 2004)
Primary intraocular lymphoma (PIOL) is a rare non-Hodgkin lymphoma which arises in the retina or the vitreous. It can occur either together with or independently of primary cerebral nervous system lymphoma (PCNSL); the incidence of the latter has significantly increased over the past three decades. PIOL remains one of the most difficult diagnoses to establish, particularly due to its ability to mimic other diseases in the eye and to the limited material which is often available for examination. The article reviews the clinical, histopathological, molecular biological and biochemical approaches to the diagnosis of PIOL. The differential diagnoses, including other lymphomatous manifestations in the eye, e.g. primary uveal lymphoma, as well as non-neoplastic uveal diseases are addressed. Furthermore, the treatment strategies for PIOL are summarised. Diagnostic progress has been made in various fields, including flow cytometry and immunocytology, cytokine analysis, and as well as molecular biological analysis of the immunoglobulin heavy and light chains using polymerase chain reaction on both fixed and non-fixed material. The optimal therapy of PIOL remains to be determined: the current trends suggest that combined radiotherapy and chemotherapy, as well as intravitreal chemotherapy, are of value. Novel therapies which may have a role in the future include oral trofosfamide. Our understanding of the pathogenesis of PIOL/PCNSL remains far from complete. Intensified efforts must be made to determine the cell of origin of PIOL, as well as to establish "molecular signatures", which could be used to decrease diagnostic delay. Further studies, possibly prospective ones, are required to establish the optimal therapy for initial and recurrent disease.